Metabolome and Microbiota Analysis Reveals the Conducive Effect of Pediococcus acidilactici BCC-1 and Xylan Oligosaccharides on Broiler Chickens - Wu, Yuqin; Lei, Zhao; Wang, Youli; Yin, Dafei; Aggrey, Samuel E.; Guo, Yuming; Yuan, Jianmin (Frontiers in Microbiology, 2021)
Xylan oligosaccharides (XOS) can promote proliferation of Pediococcus acidilactic BCC-1, which benefits gut health and growth performance of broilers. The study aimed to investigate the effect of Pediococcus acidilactic BCC-1 (referred to BBC) and XOS on the gut metabolome and microbiota of broilers. The feed conversion ratio of BBC group, XOS group and combined XOS and BBC groups was lower than the control group (P < 0.05). Combined XOS and BBC supplementation (MIX group) elevated butyrate content of the cecum (P < 0.05) and improved ileum morphology by enhancing the ratio of the villus to crypt depth (P < 0.05). The 16S rDNA results indicated that both XOS and BBC induced high abundance of butyric acid bacteria. XOS treatment elevated Clostridium XIVa and the BBC group enriched Anaerotruncus and Faecalibacterium. In contrast, MIX group induced higher relative abundance of Clostridiaceae XIVa, Clostridiaceae XIVb and Lachnospiraceae. Besides, MIX group showed lower abundance of pathogenic bacteria such as Campylobacter. Metabolome analysis showed that all the 3 treatment groups (XOS, BBC and MIX) showed lower concentrations of sorbitol and both XOS and BBC group had higher concentrations of pyridoxine levels than CT group. Besides, XOS and BBC groups enhanced the content of hydroxyphenyl derivatives 4-hydroxyphenylpyruvate 1 and 3-(3-hydroxyphenyl) propionic acid, respectively (P < 0.05). Notably, MIX group enhanced both 4-hydroxyphenylpyruvate 1 and 3-(3-hydroxyphenyl) propionic acid (P < 0.05). Thus, XOS and BBC may have a synergistic role to improve the performance of broilers by modulating gut microbiota and metabolome.